The use of the road-to-health booklet developmental screening in the detection and referral of early developmental delay in the Pelonomi hospital drainage area - Naborn, Bernice (My University, 2016)
Context: The use of the Road-to-health booklet (RTHB) developmental screening checklist may aid in the early detection of, referral and intervention for developmental delay in the primary care setting. Objective: The aim of this study was to examine the use of the new Road-to-health booklet developmental screening checklist by the nursing staff of referring clinics at any visit before being admitted to hospital. This study aimed to compare the results of nurse-completed screening checklists with those completed by a paediatrician, and to compare the referral patterns of children with a suspected developmental delay by both the nursing staff and paediatrician. This study further aimed to establish whether there was an association between caregiver concern and the identification of a delay by using the RTHB checklist by the clinic staff or the paediatrician. Design, setting and patients: A cross-sectional descriptive study of patients younger than six years of age referred to a hospital in Bloemfontein, South Africa, during May 2014 to October 2014. Methods: Children referred to Pelonomi Hospital for admission were eligible for inclusion in the study. The use and results of the RTHB developmental screening checklist completed prior to admission by the referring clinics’ nursing staff were documented. The caregivers were questioned on the development of their child. The principal investigator, who is a paediatrician, repeated the same developmental screening checklist upon referral to the hospital. The outcome of the screening checklist completion and subsequent referral patterns of the clinics’ nursing staff were compared to that of the paediatrician. Results: The RTHB developmental screening checklist was completed by their clinic prior to referral in 45/113 (40%) of the study participants. In 6/45 (13%) of cases the clinic detected a possible delay. A developmental delay was suspected by 28/113 (25%) of the caregivers. The paediatrician detected a possible developmental delay in 32/113 (28%) of the cases. There was a statistically significant difference in the proportion of children with developmental delay detected by the paediatrician versus children with developmental delay detected by the clinic (14/45 [31%] vs 6/45 [13%]; p < 0.0003). Parental concern was associated with a higher rate of identifying delays as compared to the use of the RTHB by both the paediatrician (p<0.0001) and the clinic nursing staff (p<0.0001). There was no significant difference in the referral pattern of the clinic versus the paediatrician once a possible delay had been detected. Conclusion: The RTHB developmental screening checklist is not used optimally to detect developmental delays at a primary care level.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master in Science in Medicine in Child Development. Johannesburg, 2016